Bambupreneur: Transforming Bamboo Craftsmen's Businesses into Competitive MSMEs Through Production and Financial Training - Nugraha, Adri Putra; Nadhivatuzuhro, Iqlimah; Andriyanto , Rahmad (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
The Mulya Jaya Bamboo Craftsmen Community in Ternyang Village, Sumberpucung District, Malang Regency, is a micro-business group with great potential in the bamboo craft industry. However, after four years of operation, the community still faces fundamental challenges, particularly limited production equipment (especially bamboo cutting tools) and the absence of an adequate financial recording system. These conditions lead to low production efficiency, inconsistent product quality, and difficulties for craftsmen in determining selling prices and measuring business performance accountably. This community service program aims to transform the craftsmen community into a more professional and competitive micro, small, and medium enterprise (MSME) through integrated technical and managerial training. The program focuses on two main interventions: (1) capacity-building in production by providing and training the use of more efficient bamboo cutting tools, and (2) basic business accounting training covering daily financial recording and cost of goods sold (COGS) calculation. The activity adopts an Empowerment-Based Learning model that emphasizes active participation, hands-on practice, and the development of sustainable work habits. The results indicate improved productivity, strengthened business management, and expanded market access for the community’s products in a sustainable manner.